OPTIMALISASI DISTRIBUSI BARANG MENGGUNAKAN METODE NORTHWEST CORNER (NWC) PADA PT SINAR KALIMANTAN BERAU - Vierana Neha Anggraini; Alifatul Luthfi; Shelina Irene; Mikhael Jerry Toppa; Steven Irawan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Efficient product delivery is a central component of company operations because it determines punctual customer receipt while keeping expenditure under control. As a distributor, PT Sinar Kalimantan Berau encounters operational constraints, including reduced workforce availability during employee absence, delayed fuel replenishment, and possible item loss that may interrupt shipments. This investigation evaluates the firm’s delivery arrangement using the Northwest Corner (NWC) procedure and estimates the associated cost through POM-QM. A descriptive framework was adopted, while information was obtained from direct interviews and field observation. The dataset comprises route charges, vehicle carrying limits, and order quantities at every destination. The resulting allocation assigns 500 boxes from Fleet A to Toko Celebes Mart, 10 boxes from Fleet B to Toko Celebes Mart, 290 boxes from Fleet B to Unggul Mart Durian III, and 200 boxes from Fleet C to Toko Solo Swa Sambaliung. POM-QM produces an aggregate expense of Rp64,630,000, identical to the manual computation. These results indicate that NWC, supported by POM-QM, offers a structured basis for arranging shipments according to vehicle capacity and destination requirements.